The Turkish wage curve: Evidence from the household labor force survey - Badi H. Baltagi; Yusuf Soner Baskaya; Timur Hulagu (Institute for the Study of Labor (IZA), 2011)
This paper examines the Turkish wage curve using individual data from the Household Labor Force Survey (HLFS) including 26 NUTS-2 regions over the period 2005-2008. When the local unemployment rate is treated as predetermined, there is evidence in favor of the wage curve only for younger and female workers. However, if the lagged unemployment rate is used as an instrument for current unemployment rate, we find an unemployment elasticity of -0.099. We also find a higher elasticity for younger, less educated, low experienced workers than for older, more educated and more experienced workers. Another important finding is that the wages of females in Turkey are significantly more responsive to local unemployment rates than their male counterparts.
urn:nbn:de:101:1-201104134363
Keywords: C26; J30; J60; 330; wage curve; fixed effects; instrumental variables; two-stage least squares; Lohnkurve; Regionale Lohnstruktur; Regionale Arbeitslosigkeit; Lohndifferenzierung; Schätzung; Türkei